3D printing of calcined clay-limestone-based cementitious materials. (November 2021) - Chen, Yu; He, Shan; Zhang, Yu; Wan, Zhi; Çopuroğlu, Oğuzhan; Schlangen, Erik
Abstract: This paper aims to investigate the influences of high Portland cement substitutions (>60 wt%) by low-grade calcined clay (CC) and limestone (LF) on 3D concrete printability, stiffness evolution and early-age hydration. Results show that, with the same dosage of admixtures (superplasticizer and viscosity modifier), increasing LF and CC content reduced the slump, flowability and initial material flow rate, and significantly improved the buildability of fresh mixtures, which can be attributed to the reduced water film thickness (WFT). Furthermore, the stiffness evolution and SSA total development up to the first 3 h were accelerated by increasing CC content, which can also be linked to the change of WFT, and consumption of superplasticizer for the dispersion induced by hydration products. Additionally, the dilution effect on compressive strength and hydration caused by the high cement replacement was observed.